Market performance and volatility during the Covid-19 pandemic in Vietnam: A sector-based analysis - Ngoc Hong Nguyen; Nam Thanh Vu; Quan Tran; Thao Tran; Duc Hong Vo (Cogent Business & Management, 2022)
The effects of the Covid-19 pandemic on firms' performance have been extensively investigated. However, the abnormal returns and volatilities across industries during different waves of the pandemic using an event study have largely been neglected in the existing literature, particularly for Vietnam. As such, this study investigates the impact of the pandemic on the performance and volatility of the entire stock market and across 13 industries during the four Covid-19 outbreaks in Vietnam, including 23 January 2020 (the first wave), 25 July 2020 (the second wave), 28 January 2021 (the third wave), and 27 April 2021 (the fourth wave). An event study is used on the sample of 404 listed firms. Our findings indicate that the announcements of the first three outbreaks adversely affect the stock market returns and volatilities, leading to the firm's financial distress. Furthermore, we find that the market has responded slowly to the fourth wave compared to the first three waves. However, the effects of this fourth wave have lasted longer. Agriculture, Construction, Real Estate, and Manufacturing are the most affected industries, whilst Information and Technology and Financial and Insurance Services are the most resilient industries across the four waves of the pandemic in Vietnam. Furthermore, results from our analysis indicate that the government's announcement of ending the lockdown of Ho Chi Minh City in October 2021 has positively affected the stock market performance in Vietnam.
Keywords: 650; COVID-19 pandemic; event study; market performance; Vietnam's industries; volatility